Monoclonal Antibodies in Clinical Oncology - Dalle, S.; Thieblemont, C.; Thomas, L.; Dumontet, C. (Anti-Cancer Agents in Medicinal Chemistry, 2008)
Monoclonal antibodies have yet considerably modified the field of clinical oncology. The growing knowledge of key cellular pathways in tumor induction and progression, targeted therapies represent an increasing proportion of new drugs entering clinical trials. Some molecules such as trastuzumab, rituximab, alemtuzumab, cetuximab are now widely used in clinical practice. These antibodies are now tested in different indications alone or in combination with standard chemotherapy. They are also developed for the treatment of inflammatory diseases (rituximab). Numerous others antibodies are currently in pre-clinical and clinical development phases for several malignancies including renal carcinoma, melanoma, lymphomas, leukaemia, breast, ovarian and colorectal cancer. An alternative approach is to conjugate the monoclonal antibody to a toxin, a cytotoxic agent, or a radioisotope. In other cases these antibodies aim to modify the tumour microenvironnement through inhibition of angiogenesis or enhancing host immune response against cancer. If the molecule targeted by the antibodies is clearly identified, most often the precise mechanism of action of these immunoglobulins is not fully understood.They can have direct effects in inducing apoptosis or programmed cell death. They can block growth factor receptors, efficiently arresting proliferation of tumor cells. Indirect effects include recruiting cells that exert cytotoxicity, such as monocytes and macrophages (ADCC). Monoclonal antibodies also bind complement, leading to toxicity known as complement dependent cytotoxicity (CDC).The side effects associated with these new treatments were in part foreseeable depending on the affected cell or function. But new or surprising side effects emerged from clinical studies. We present an overview of the monoclonal antibodies used in clinical oncology or currently in development phases. We particularly focus on recent development including new indications, clinical trial results and specific side effects of monoclonal antibodies used in the treatment of cancer.
Keywords: cancer